A Pedagogical Study of Positive Discipline in Post-Reunification Parenting : Raising Resilient Children - Samosir, Irniyati; Sudrajat, Jajat; Wahyudin, Uyu; Sardin, Sardin; Sudiapermana, Elih; Robandi, Babang (Universitas Pendidikan Mandalika, 2025)
This study aims to examine the application of positive discipline in post-reunification care from a pedagogic perspective, focusing on how this approach can improve the relationship between parents and children and support children's emotional and social development. This research used a qualitative approach with a case study method. Data were collected through semi-structured in-depth interviews and participant observation of four families in Bandung City who had experienced reunification after a significant period of separation. Data were analyzed through qualitative data analysis, including stages data reduction, data display, and conclusion drwaing and verification. The results showed that the application of positive discipline significantly helped improve communication and understanding between parents and children. Strategies such as open communication, appreciation of children's efforts, and the use of natural and logical consequences proved effective in improving family dynamics. This study provides deep insights into the application of positive discipline in the context of family reunification, which is still rarely explored. The findings can inform the development of parent training programs and policies that support the well-being of reunified families.